Analysis of seaweed gels and characteristics of gel extraciton wastewater - Diep Minh Tam; Edwards, Peter; Samorn Muttamara; Nguyen, Cong Thanh; The Government of Japan (Bangkok : Asian Institute of Technology, 1978)
An investigation was made of three genera of seaweeds from Thailand, Gracilaria, Sargassum and Hypnea, sources of agar, algin and carrageenan, respectively. The potential gel yield of these seaweeds was assessed and their gel characteristics, namely gel strength, gelation temperature, melting temperature and color, were studied. Gracilaria seems to have a great promise of exploitation for local utilization, especially those from Chum Porn, Prachuab Khirikhan, Song Khla and Trad. The yield of Gracilaria from these locations varied from high, 30%,to very high, 51%, while their gel strength and color were equal or better than some commercial agars from Japan and the Philippines. Sargassum from Suras Thani also showed some similar promise due to its sodium alginate yield of 21 to 31%, which was generally higher than the yields reportedly obtained from the same genus in some other countries such as India and Taiwan. The Hypnea species did not possess good qualities in their carrageenan although the yield varied from low, 22%, to quite high, 46%. Only one sample from Narathiwas might have potential use in the future. The wastes from the extraction processes were found to be very polluting due to their high contents of total solids , from 5,000 to 10,000 mg/t; chemical oxygen demand values from 2,000 to 5,600 mg/t; relatively high organic matter contents as indicated by volatile solids values from 1400 to 2800 mg/t; a presence of brown color from 300 to 500 units, and some residues of formaldehyde in the case of the al gin extraction waste. Based on the results of waste characteristic analyses, a general treatment procedure was proposed.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Sc.) - Asian Institute of Technology, 1978
Keywords: Sewage -- Analysis; Marine algae